Methamphetamine psychosis: Insights from the past - McKetin, Rebecca (Wiley-Blackwell Publishing Ltd., 2018)
Background and aims: To review early case reports and experimental inductions of amphetamine and methamphetamine psychosis, prior to the prohibition of these drugs, to gain a better understanding of the nature and aetiology of methamphetamine psychosis. Methods: Papers considered were historical case reports and case series of psychosis relating to the use and misuse of prescription amphetamine, focusing upon papers by Young & Scoville (1938), Connell (1958), and three subsequent experimental studies published in the early 1970s (Griffith 1972, Angrist & Gershon 1970 and Bell 1973), where psychosis was induced in volunteers using high-dose amphetamine and methamphetamine. Results: High-dose methamphetamine and amphetamine can result in a paranoid psychosis which remits rapidly (within days) of discontinuing use. The central feature is paranoia occurring in a clear state of consciousness. This may be accompanied by other psychotic symptoms (e.g. hallucinations). Pre-existing schizophrenia is not necessary, and the syndrome is not due to sleep deprivation. Conclusions: Research findings from the 1930s to the 1970s suggest that paranoid psychosis should be considered a probable consequence of high-dose methamphetamine use. Individuals who experience psychotic symptoms for any substantive period after intoxication has ended should be suspected of having a functional non-organic psychosis, or a latent vulnerability thereto.